Studies on Dilutors vis-a-vis Freezability of Patanwadi Ram Semen: II. Effect on Spermatozoal Enzyme Leakage - NEMA, S P; DHAMI, A J; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
The effects of dilutors, rams, stages of freezing process and their interactions were studied in 30ejaculates (6/ram) in a 3x5x3 factorial experiment for motility and leakage of spermatozoa) enzymes duringcryopreservation of Patanwadi ram semen. The 3 diluents used with 20% egg yolk and 4% glycerol were trisfructose citric acid egg yolk glycerol (TFCEG), phosphate buffer glucose fructose sodium citrate potassiumchloride egg yolk glycerol -a synthetic phosphate medium (Phos) and sodium citrate glucose egg yolkglycerol (SCGEG). The effects of dilutors, rams, stages of freezing (initial, prefreeze and post-thawed) and·their two-way interactions were highly significant on sperm motility and leakage ·of LOH, GOT and AKPenzymes. Minimum LOH leakage (383.2 ± 7.28 IU/billion sperms) and maximum post-thaw.motility (36.67± 1.13%) was observed in TFCEG. diluent followed by Phos (31.00 ± 1.43%) and SCGEG (19.83 ± 0.85%)diluents, although GOT and AKP leakage was minimum in Phos and maximum in TFCEG diluent. Oilutor xram x stage interaction was also significant for all 3 enzymes. Rams having better sperm motility at dilutionstage could express equally good post-thaw motility in Phos diluent. ·Further, the observations indicated thatthough motility was significantly higher in TFCEG diluent, the remaining attributes, except LOH leakage,were more congenial for freezing process in Phos diluent.
Keywords: Dilutors; Freezability; Dehydrogenase; Phosphatase,; Transaminase; Ram semen